Disinflationary booms? - Christian Merkl (Kiel Institute for the World Economy (IfW), 2013)
This paper shows that announced credible disinflations under inflation targeting lead to a boom in a standard New Keynesian model (i.e. a disinflationary boom). This finding is robust with respect to various parameterizations and disinflationary experiments. Thus, it differs from previous findings about disinflationary booms under monetary targeting.
Keywords: E30; E31; 330; Disinflation; Disinflationary Boom; Inflation Targeting